Pengaruh Lingkungan Kerja, Komunikasi, dan Keseimbangan Hidup terhadap kinerja karyawan - Amal Vieri; Michael Abed Nego Harianja; Alan Setiawan; Oktavianus Aldi Renaldi; Steven Keane (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of the work environment, communication, and work-life balance on employee performance. In the context of globalization and intense business competition, employee performance is a key factor in determining organizational success. A good work environment, both physical and non-physical, plays a crucial role in enhancing employee motivation and job satisfaction. This research employs a quantitative method using convenience sampling and data collection through questionnaires. The analysis results indicate that a conducive work environment, effective communication, and a balance between work and personal life have a positive and significant impact on employee performance. A comfortable and supportive work environment, along with good interpersonal relationships, can boost employee morale and productivity. Additionally, a healthy work-life balance helps reduce stress and improve mental health, which in turn contributes to better performance. These findings provide insights for companies to create better work environments that not only enhance performance but also overall employee well-being. This research is expected to serve as a reference for organizations in designing more effective human resource management strategies.